Teacher Strategies in Improving Interest in Reading Al-Quran Hadis - Sugisman, Sugisman; Supardi, Nasruddin; Irwandi, Adi (Civiliza Publishing, Indonesia., 2025)
Islamic Education Teachers 'Strategy Interest in Reading Al-Quran Hadis. The importance of reading the Al-Quran Hadis as a guide for our lives, especially Muslims. The purpose of this study is to develop teacher strategies to improve the ability to read. Describe the supporting and inhibiting factors for reading. This research uses a qualitative type of research through the observation, interview and documentation approach. The results of the research are known from the stage of presenting data and analyzing the interest in reading the strategies to what extent the learners' knowledge of its importance reading Al-Quran Hadis, to the process of increasing interest in reading Al-Quran Hadis and the existence of supporting and inhibiting factors in the field were carried out well in the Islamic Religious Education lesson. The research results show that the teachers' approaches to increasing interest in reading the Quran and Hadith among students at include habituation and individual approaches. The methods used are Drill and Sorogan. Supporting factors include facilities and infrastructure, extracurricular activities, and student motivation.